The seventy great inventions of the ancient world - Fagan, Brian M. (London Thames & Hudson, 2004)
Stone choppers, eyed needles camel saddles chariots and contraceptives the past is paved with remarkable inventions. The latest book in this popular series takes us on an eye opening and unusual journey through early human innovations--some fundamental and others intriguing or bizarre. An international team of scientists, archaeologists, and historians reveals seventy of the most extraordinary inventions from two and a half million years ago up to the early medieval period. The book begins with the basic technologies of stone, fire, wood working ceramics metallurgy glass and weaving we watch stone Age flint-snappers at work and look over the shoulders of early metal workers as they fabricate glittering ornaments in copper and gold. Some of the most fundamental questions of the post are addresses. How and where did agriculture evolve? How did Romans and others heat and plumb their dwellings? what roles did cooking food preservation, and fermentation play in the development of ancient cuisine? how did the wheel and cart change human life? when did long distance seafaring begin? Later sections look at the origins of hunting, war and sport, art and science and personal adornment weapons of war evolved from spears bows and arrows to swords, shields, catapults and cross bows.
Includes bibliographical references (p.291-296) and index
Keywords: Inventions -- History; Technology -- History